2005
DOI: 10.1177/230949900501300115
|View full text |Cite
|
Sign up to set email alerts
|

Dysplasia Epiphysealis Hemimelica of the Talus: Two Case Reports

Abstract: Trevor's disease, also known as dysplasia epiphysealis hemimelica, is an uncommon skeletal developmental disorder representing an osteochondroma occurring in one or more epiphyses. We present 2 cases of dysplasia epiphysealis hemimelica in an 8-year-old female and a 12-year-old male who suffered from a hard swelling of the ankle joint. The female patient was treated by surgical excision and the male patient conservatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Even though OC is the most common of all benign bone tumours and represents 10% to 15% of all bone tumours, DEH is rarer. DEH has a reported incidence of 1 : 1.000.000 [17, 18]. Despite DEH's rarity, including our case, 73 authors have reported 144 cases from 1926 to 2013.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Even though OC is the most common of all benign bone tumours and represents 10% to 15% of all bone tumours, DEH is rarer. DEH has a reported incidence of 1 : 1.000.000 [17, 18]. Despite DEH's rarity, including our case, 73 authors have reported 144 cases from 1926 to 2013.…”
Section: Discussionmentioning
confidence: 78%
“…The age of 8 is also typical for first presentation. Most of the cases appear between the ages of 2 and 8 but cases have been reported in patients from 2 months to 40 years old [8, 18, 22–24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…He also speculated that the peculiarity in vascular arrangement of the epiphysis was responsible for the tendency of this lesion to be asymmetrically confined to only one side of the joint, preferentially the medial side 6. Bhosale et al ,8 in 1933, conjectured that the cartilage of an epiphysis of a long bone is formed from a narrow zone ‘mitotic annulus’, where cartilage cells are actively dividing. These cells in the mitotic annulus eventually disintegrate, and together with the matrix they give rise to the main constituent of synovial fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Bhosale et al 13 suggested excision if the lesion caused disability and arthrodesis of the ankle may be appropriate with extensive involvement of the talus. Trevor3 and Kettelkamp et al 14 suggested an arthrodesis for patients developing degenerative joint disease.…”
Section: Discussionmentioning
confidence: 99%